The Development of an Organizational Culture that Encourages the Application of Good Management Practices Allow Outstanding Business Innovation Performance: A Theoretical Approach and Model of Teaching, Research and Outreach Adopted in the UNA-INNOVA Project of Expertise in Human Resources Management of the Universidad Nacional - Figueroa-Araya, Christian (2016)
Business success is directly related  to the ability to adapt and respond to the needs of the market or with their economic possibilities to fund the change through research, development and innovation.  The national scene reflects a business park full of small and medium-sized companies with few possibilities to invest in I+D+I. However, the company innovation achievement goes further than managerial disposition, company strategy, external variables or the assignation of financial resources . On the contrary, it requires an organizational layout who gives enough flexibility to manage creativity and foment innovation, a well done organizational disposition leads to the development of management skills, which improve innovative progress. A correct organizational disposition that dowry of enough flexibility that allows managing creativity and encourage innovation.   In agreement with Sánchez and Lopez  (2013), good skills is visible, which means on one hand that it has public and institutional  recognition, on the other hand it can be documented and record, cause it has positive and verifiable results. In accordance with Epper and Bates (2014), these skills may be extrapolated in different contexts. The following article summarizes the argument theoretical-methodological of project UNA-INNOVA attached to the mastery in administration of human resources of the National University, which seeks the identification and recollection of skills dedicated to outstanding management that can be emulated or contextualized by Costa Rican companies. By using the linkage teaching investigation-extension, UNA-INNOVA pretends to give a hand that helps Costa Rican companies to obtain tools that boost the change and organizational flexibility so they can confront the actual business context.